Real-Time Simulation of the Initial Dynamic Model of CE in ePHASORsim: Issues and Troubleshooting - Ramirez-Gonzalez, M.; Obushevs, A.; Sevilla, F. R. Segundo; Korba, P. (Conference proceedings (IEEE International Scientific Conference on Power and Electrical Engineering of Riga Technical University. Online), 2024)
Power system simulation models are crucial for planning and operational studies. Besides, due to the advantages of real-time and hardware-in-the-loop testing where a set of physical components are integrated into a software ecosystem for different research purposes, there is an increasing need to transfer large and practical power system models available in offline platforms to real-time environments. On this subject, this paper presents the main issues encountered by the authors when transferring the Initial Dynamic Model of Continental Europe from an available P SS/E database to OPAL-RT's ePHASORsim. Power flow and dynamic simulation troubleshooting was carried out to allow the appropriate model deployment in the target real-time platform. Simulation results from selected study cases illustrate the successful implementation and execution of the considered power system model in an OPAL-RT real-time simulator setup based on the OP5600 equipment.